Membrane Protein Activity Induces Specific Molecular Changes in Nanodiscs Monitored by FTIR Difference Spectroscopy - Baserga, Federico; Vorkas, Antreas; Crea, Fucsia; Schubert, Luiz; Chen, Jheng-Liang; Redlich, Aoife; La Greca, Mariafrancesca; Storm, Julian; Oldemeyer, Sabine; Hoffmann, Kirsten; Schlesinger, Ramona; Heberle, Joachim (Frontiers in Molecular Biosciences, 2022)
It is well known that lipids neighboring integral membrane proteins directly influence their function. The opposite effect is true as well, as membrane proteins undergo structural changes after activation and thus perturb the lipidic environment. Here, we studied the interaction between these molecular machines and the lipid bilayer by observing changes in the lipid vibrational bands via FTIR spectroscopy. Membrane proteins with different functionalities have been reconstituted into lipid nanodiscs: Microbial rhodopsins that act as light-activated ion pumps (the proton pumps NsXeR and UmRh1, and the chloride pump NmHR) or as sensors (NpSRII), as well as the electron-driven cytochrome c oxidase RsCcO. The effects of the structural changes on the surrounding lipid phase are compared to mechanically induced lateral tension exerted by the light-activatable lipid analogue AzoPC. With the help of isotopologues, we show that the ν(C=O) ester band of the glycerol backbone reports on changes in the lipids’ collective state induced by mechanical changes in the transmembrane proteins. The perturbation of the nanodisc lipids seems to involve their phase and/or packing state. 13C-labeling of the scaffold protein shows that its structure also responds to the mechanical expansion of the lipid bilayer.